Gesture influences the processing of figurative language in non-native speakers: ERP evidence - Ibañez, Agustin Mariano (2010)
Gestures should play a role in second language comprehension, given their importance in conveying contextual information. In this study, the N400 and the LPC were evaluated in a task involving the observation of videos showing utterances accompanied by gestures. Students studying advanced (G-High participants) and basic German (G-Low participants) as a second language were investigated. The utterance-gesture congruence and metaphoric meaning of content were manipulated during the task. As in previous ERP reports with native speakers, metaphorical expressions were sensitive to gestures. In G-Low participants, no modulation in the 300-500 ms window was observed, and only a modest effect was observed for the 500-700 ms window. More subtle differences of verbal expression were not processed in this group. Consistent with previous reports of the same paradigm with native speakers, the N400 from G-High group discriminated both congruent and incongruent gestures as well as literal and metaphorical sentences. Our results suggest that semantic processing is robust in the learning of a second language, although the amplitude modulation and latency of ERPs might depend on the speaker's proficiency level. © 2010 Elsevier Ireland Ltd. All rights reserved.